Australian Pastures Genebank – Temperate Species Regeneration - Rowan Smith; Gary Martin (2017)
The Australian Pastures Genebank (APG) is Australia’s first national collection of pasture and forage genetic resources and was opened in 2014. Since then more than 83,000 accessions have been transferred from State based collections to the genebank. Approximately 75,000 of the 83,000 are unique accessions, found in no other genebanks worldwide. This makes the collection incredibly important for plant breeders. Furthermore, Tasmania’s contribution is worth noting with over 5000 packets of seed from 2829 accessions transferred from the DPIPWE collection. Of these 2829 accessions, approximately 70% are unique to the APG. TIA has conducted regeneration activities on temperate grasses for the APG since 2015. This involves the multiplication of seed and characterisation of accessions for the APG. Seed and associated data is made available to researchers and plant breeders on request. Seed is also backed-up in the Global Seed Vault in Svalbard, Norway. This presentation will summarise TIA’s involvement in the transfer of germplasm to the APG from DPIPWE and also the regeneration activities conducted.